Investigações sobre seguimento de olhar e tomada de perspectiva em crianças com desenvolvimento típico e com autismo - Silveira, Carolina Coury (Universidade Federal de São Carlos, 2019)
This thesis was written in the form of a compendium of scientific texts. It included four studies that supported the planning and implementation of investigations that aimed to identify critical parameters in the establishment of the repertoires of looking direction and Perspective Taking for children with and without autism. First, the first experiment investigated whether changes in a procedure already replicated for multiple exemplar training would enable the verification of generalized operant characteristics for two children within Autistic Spectrum Disorder (ASD) (Study 1). Second, observing a lack of studies in joint attention literature using a single-subject design, the aim was to investigate changes individually in eye-tracking patterns (via an eye-tracking device). Additionally, the vast majority of the studies in the area focused on the characterization of eye tracking in assessment in isolated tasks, with little explored as the eye-tracking patterns varied throughout the learning of responses, which guided the research question of Study 2. The first two studies explored joint attention responses (i.e., following the direction of someone's gaze), and they aimed to investigate and improve the social interaction behavior in very young children and provided relevant information for planning intervention for children with autism. However, social interaction, in general, can include many more complex responses that were not addressed in both previous investigations (Studies 1 and 2). Thus, for a broad interpretation of this phenomenon, in the sequence, a theoretical investigation was proposed. This investigation aimed to develop a functional analysis based on the Multi-Dimensional Multi-Level (MDML) framework for relational repertoires. This analysis allowed to establish responses for the development of Perspective-Taking (Study 3). Finally, the hypothesis raised about the minimum relational repertoires necessary for establishing Perspective-Taking in the previous theoretical research inspired an empirical investigation (Study 4). This last study involved the development of tasks to assess relational repertoires in a child with and another without autism with a similar development profile. Besides, this study also aimed to teach and develop the necessary relational repertoire that potentially would enable the presentation of Perspective-Taking, which were deficient for the child with autism. Subsequently, this teaching procedure effects for the behavioral repertoire of the participant were evaluated. In summary, the present thesis explored both fundamental and complex repertoire, crucial for the proper establishment of social interactions: gaze-following responses (Studies 1 and 2), and relational responses for Perspective-Taking (Studies 3 and 4). Both repertoires investigated seem to be fundamental for overcoming significant social barriers in individuals with autism.
Investigations on eye tracking and perspective taking with children with typical development and autism
Keywords: Tomada de perspectiva; Treino de múltiplos exemplares; Seguimento de direção do olhar; Rastreamento de olhar; Autismo; Autism; Perspective taking; Multiple exemplar training; Gaze following; Eye-tracking; CIENCIAS HUMANAS::PSICOLOGIA